Effects of using Contextual Clues on English Vocabulary Retention and Reading Comprehension - Tuyen, Le Van; Huyen, Vo ThiNgoc (International Journal of English Literature and Social Sciences (IJELS), 2019)
Vocabulary is one of the most pivotal but complex aspects to English language students. To achieve the knowledge of English vocabulary requires students to have specific learning strategies.Using contextual clues is considered one of the essential strategies that can guide students to figure out the meanings of unknown words. This study, therefore, aims at exploring the effects of using contextual clues on English-majored students’ vocabulary retention and reading comprehension at Bac Lieu University, Vietnam (henceforth called BLU). Sixtytwo second-year English majored students were randomly selected for the study and divided into the experimental and control groups. Quantitative data were collected through three instruments namely, pre-test, experiment and post-test. The results revealed that using contextual clues positively affected students’ vocabulary retention and reading comprehension. This study is expected to shed light on students’ vocabulary and reading’s improvement through the use of contextual clues in Vietnamese context and in other similar educational contexts as well.